Validation of Porcine Knee as a Sex-specific Model to Study Human Anterior Cruciate Ligament Disorders - Kiapour, Ata M. (Clin Orthop Relat Res, 2014)
BACKGROUND: Animal models have long been considered an important modality for studying ACL injuries. However, to our knowledge, the value of these preclinical models to study sex-related phenomena associated with ACL injury and recovery has not been evaluated. QUESTIONS/PURPOSES: We asked whether (1) prominent anatomic and (2) biomechanical factors differ between female and male porcine knees, particularly those known to increase the risk of ACL injury. METHODS: Eighteen intact minipig knees (nine males, nine females) underwent MRI to determine the femoral bicondylar width, intercondylar notch size (width, area and index), medial and lateral tibial slope, ACL size (length, cross-sectional area, and volume), and medial compartment tibiofemoral cartilage thickness. AP knee laxity at 30°, 60°, and 90° flexion and ACL tensile structural properties were measured using custom-designed loading fixtures in a universal tensile testing apparatus. Comparisons between males and females were performed for all anatomic and biomechanical measures. The findings then were compared with published data from human knees. RESULTS: Female pigs had smaller bicondylar widths (2.9 mm, ratio = 0.93, effect size = −1.5) and intercondylar notches (width: 2.0 mm, ratio = 0.79, effect size = −2.8; area: 30.8 mm(2), ratio = 0.76, effect size = −2.1; index: 0.4, ratio = 0.84, effect size = −2.0), steeper lateral tibial slope (4.3°, ratio = 1.13, effect size = 1.1), smaller ACL (length: 2.7 mm, ratio = 0.91, effect size = −1.1; area: 6.8 mm(2), ratio = 0.74, effect size = −1.5; volume: 266.2 mm(3), ratio = 0.68, effect size = −1.5), thinner medial femoral cartilage (0.4 mm, ratio = 0.8, effect size = −1.1), lower ACL yield load (275 N, ratio = 0.81, effect size = −1.1), and greater AP knee laxity at 30° (0.7 mm, ratio = 1.32, effect size = 1.1) and 90° (0.5 mm, ratio = 1.24, effect size = 1.1) flexion compared with their male counterparts. These differences were significant for all parameters (p ≤ 0.04). Observed sex-related differences were similar to those reported for the human knee. CONCLUSIONS: Significant differences exist between knees of male and female pigs with respect to prominent anatomic and biomechanical factors. Our findings strongly agreed with published data regarding human knees. CLINICAL RELEVANCE: The findings highlight the use of the porcine large animal model to study the role of sex on ACL injuries and surgical outcome. This validated preclinical model may facilitate the development of novel, sex-specific interventions to prevent and treat ACL injuries for male and female patients.